Utilization Of Iot Technology In An Automated Fertilizetion System To Improve Efficiency And Productivity Of Tobacco Plants - Ayuni; Lalu Delsi Samsumar; Zaenudin; Ahmad Subki; Ardiyallah Akbar (Journal of Computer Science and Informatics Engineering, 2024)
The plantation crop called tobacco is the main component needed to make cigarettes. The development and quality of tobacco plants are highly dependent on environmental factors, including sufficient soil moisture and adequate nutrition. Excessive soil moisture and lack of nutrients can cause plants to wither and die, so an IoT-based automatic fertilization system is needed. This research designs an automatic fertilization system that utilizes the NodeMCU ESP8266 integrated with the Blynk application. Soil Moistute sensor is used to measure or detect soil moisture content, RTC is used for scheduling fertilization, and Relay is used to turn on the pump automatically. Prototyping method is applied in this system, starting from requirement gathering to final evaluation. The system succeeded in increasing the efficiency and productivity of tobacco plants, as well as providing convenience for farmers in managing fertilization and watering automatically